Acoustic biomass estimation of mesopelagic fish: Backscattering from individuals, populations, and communities - Davison, P.; Koslow, J.; Kloser, Rudy (Oxford University Press 2009, 2015)
© 2015 International Council for the Exploration of the Sea 2015. All rights reserved. For Permissions, please email: journals.permissions@oup.com.Acoustic survey methods are useful to estimate the distribution, abundance, and biomass of mesopelagic fish, a key component of open ocean ecosystems. However, mesopelagic fish pose several challenges for acoustic biomass estimation based on their small size, wide depth range, mixed aggregations, and length-dependent acoustic reflectance, which differentiate them from the larger epipelagic and neritic fish for which these methods were developed. Foremost, there is a strong effect of depth on swimbladder resonance, so acoustic surveys of mesopelagic fish must incorporate depth-stratification. Additionally, the 1-3 cm juveniles of many species are not only more abundant, but can also be stronger acoustic backscatterers than the larger adults that comprise most of the biomass. The dominant species in terms of biomass may thus be weak acoustic backscatters. Failure to properly incorporate depth, the full size distribution, and certain less-abundant species into mesopelagic acoustic analyses could lead to errors in estimated biomass of up to three orders of magnitude. Thus, thorough validation, or "ground-truthing ", of the species composition, depth structure, population size distribution, capture efficiency of the sampling device, and acoustic properties of the fish present is critical for credible acoustic estimates of mesopelagic fish biomass. This is not insurmountable, but requires more ancillary data than is usually collected.